Safety of dupilumab in patients with atopic dermatitis: expert opinion. Issue 9 (2nd September 2021) - Francuzik, Wojciech; Alexiou, Aikaterina; Worm, Margitta
ABSTRACT: Introduction : Dupilumab, the first biologic drug to be approved for the treatment of moderate to severe atopic dermatitis in adolescents and adults, has shown efficacy and safety in clinical trials. Data on long-term safety is limited but crucial for pharmacovigilance. Therefore, we performed this review to evaluate available real-world data on the long-term safety of dupilumab in atopic dermatitis. Areas covered : PubMed and Google Scholar databases were searched for randomized controlled clinical trials (RCTs), observational studies, case series, and case reports regarding the use of dupilumab for the treatment of atopic dermatitis. Adverse events were summarized and critically evaluated. Expert opinion : Atopic dermatitis patients receiving dupilumab reported ocular surface disease more often than patients receiving placebo. Real-world data show previously unreported adverse events (blood eosinophilia, rosacea-like skin lesions, weight gain), but their mechanistic association to dupilumab treatment still requires clarification. Cutaneous T-cell lymphomas occurring under the therapy with dupilumab might be unrelated to the drug use itself but long-term follow-up data of large patient cohorts is necessary to rule out such possibility. Real-world data show that dupilumab is well tolerated in atopic dermatitis; however, ocular adverse events are not rare. Registries are needed to monitor future adverse events.